Establishing Regional Fiscal Autonomy Through Improving the Quality of Financial Reports and Human Resource Competence: Empirical Evidence from Indonesia - Hefisia Amanda; Rudy Usman; Andi Chairil Furqan; Selmita Paranoan (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study reveals testing in budget management and apparatus resources through the quality of financial reports and the quality of human resources that affect the level of regional Autonomy. The study uses a quantitative approach through data collection from 542 local governments in Indonesia during the 2021-2022 period, with a total of 1,084 observations analyzed using multiple linear regression with STATA-17 software. The test results reveal that, specifically, the quality of financial reports and the Human Development Index as a representation of human resource quality have a positive and significant relationship in shaping regional fiscal Autonomy. This indicates that increasing the transparency and accountability of financial reports and strengthening human resource capacity will strengthen the ability of local governments to finance development independently without excessive dependence on central transfers. Local governments with good financial report quality, as evidenced by fair audit results without exceptions and supported by competent human resources, are better able to optimize local revenue, manage expenditures efficiently, and improve community welfare. This study emphasizes the importance of improving the competence of officials and applying the principle of accountability in the preparation of financial reports as key strategies for strengthening fiscal Autonomy and supporting the achievement of sustainable regional development.